Priority Strategies for Sustainable Community-Based Ecotourism Management on Kaniungan Besar Island, Indonesia - Sri Wahyuni, Sri; Susilo, Heru; Erwiantono, Erwiantono (Sodality: Jurnal Sosiologi Pedesaan, 2022)
The primary objectives of this study was to identify business models to serve as the basis and offering alternative planning strategies for managing sustainable eco-tourism. To support these objectives, some methods were employed, including field observations and in-depth interviews applying questionnaires with stakeholders and visitors. Also, BMC and QSPM integration models were applied to determine the main alternative strategies. Results revealed that the existing eco-tourism management did not fully resolve the weaknesses and threats. Thus, it is also not in line with the sustainable eco-tourism requirements. However, current management strategies in the study area will likely improve and achieve maximum progress if stakeholders consider its opportunities and strengths. The most priority for the strategy for sustainable eco-tourism management is formulating model of carrying capacity.